Peran Guru Pendidikan Agama Islam dalam Mengatasi Kesulitan Siswa Membaca Al-Quran (Studi Kasus SMA Sunan Ampel Punggur Lampung Tengah) - Khasanah, Hilma Risyatul; Setiawan, Dedi; Wijaya, Adi (CV. Creative Tugu Pena, 2024)
The difficulties experienced by students in reading the Al-Qur'an are students' difficulties in articulating the hijaiyah letters which correspond to the makharijul letters, students' difficulties in understanding the combined hijaiyah letters, students' understanding of the science of recitation is still lacking, students' lack of motivation to read al-Qur'an. Qur'an, the law of long and short letters. The aim of this research problem is to determine the role, application of learning and evaluation of Islamic religious education teachers in overcoming students' difficulties in reading the Al-Qur'an at Sunan Ampel Punggur High School, Central Lampung. This type of research is field research. This sampling technique research data can be collected by researchers through field data, namely research subjects and research objects, statistically valid samples using purposive sampling techniques. Based on the results of the research analysis of this problem, the results of the research are that students can read the Al-Qur'an fluently, correctly in pronunciation of mahraj, hijaiyah letters, long and short letters, the knowledge of recitation, and can have a good influence on the quality of memorizing the Al-Qur Students. It has an impact on teaching and learning activities that are managed by teachers quite well in increasing students' understanding and mastery of the text of the verses of the Koran on a regular basis, enabling students' progress in reading, understanding and memorizing the Koran. Keywords: Reading Al Quran, Role of Teachers, Difficulties Reading Al Quran